A low-protein maternal diet during gestation affects the expression of key pancreatic β-cell genes and the methylation status of the regulatory region of the MafA gene in the offspring of Wistar rats - Sosa-Larios, Tonantzin C.; Ortega-Márquez, Ana L.; Rodríguez-Aguilera, Jesús R.; Vázquez-Martínez, Edgar R.; Domínguez-López, Aaron; Morimoto, Sumiko (Frontiers in Veterinary Science, 2023)
Maternal nutrition during gestation has important effects on gene expression-mediated metabolic programming in offspring. To evaluate the effect of a protein-restricted maternal diet during gestation, pancreatic islets from male progeny of Wistar rats were studied at postnatal days (PND) 36 (juveniles) and 90 (young adults). The expression of key genes involved in β-cell function and the DNA methylation pattern of the regulatory regions of two such genes, Pdx1 (pancreatic and duodenal homeobox 1) and MafA (musculoaponeurotic fibrosarcoma oncogene family, protein A), were investigated. Gene expression analysis in the pancreatic islets of restricted offspring showed significant differences compared with the control group at PND 36 (P < 0.05). The insulin 1 and 2 (Ins1 and Ins2), Glut2 (glucose transporter 2), Pdx1, MafA and Atf2 (activating transcription factor 2), genes were upregulated, while glucokinase (Gck) and NeuroD1 (neuronal differentiation 1) were downregulated. Additionally, we studied whether the gene expression differences in Pdx1 and MafA between control and restricted offspring were associated with differential DNA methylation status in their regulatory regions. A decrease in the DNA methylation levels was found in the 5’ flanking region between nucleotides -8118 to -7750 of the MafA regulatory region in restricted offspring compared with control pancreatic islets. In conclusion, low protein availability during gestation causes the upregulation of MafA gene expression in pancreatic β-cells in the male juvenile offspring at least in part through DNA hypomethylation. This process may contribute to developmental dysregulation of β-cell function and influence the long-term health of the offspring.